Safety and COVID-19 Symptoms in Individuals Recently Vaccinated with BCG: a Retrospective Cohort Study - Simone J.C.F.M. Moorlag; Rosanne C. van Deuren; Cornelis H. van Werkhoven; Martin Jaeger; Priya Debisarun; Esther Taks; Vera P. Mourits; Valerie A.C.M. Koeken; L. Charlotte J. de Bree; Thijs ten Doesschate; Maartje C. Cleophas; Sanne Smeekens; et al. (Cell Reports Medicine, 2020)
Summary: Bacille Calmette-Guérin (BCG) induces long-term boosting of innate immunity, termed trained immunity, and decreases susceptibility to respiratory tract infections. BCG vaccination trials for reducing SARS-CoV-2 infection are underway, but concerns have been raised regarding the potential harm of strong innate immune responses. To investigate the safety of BCG vaccination, we retrospectively assessed coronavirus disease 2019 (COVID-19) and related symptoms in three cohorts of healthy volunteers who either received BCG in the last 5 years or did not. BCG vaccination is not associated with increased incidence of symptoms during the COVID-19 outbreak in the Netherlands. Our data suggest that BCG vaccination might be associated with a decrease in the incidence of sickness during the COVID-19 pandemic (adjusted odds ratio [AOR] 0.58, p < 0.05), and lower incidence of extreme fatigue. In conclusion, recent BCG vaccination is safe, and large randomized trials are needed to reveal if BCG reduces the incidence and/or severity of SARS-CoV-2 infection.